Determination of Antihistamine in Tablets Preparation by Fluorescence Quenching Method - Aditya Singgih Raharjo; Asmiyenti Djaliasrin Djalil; Pri Iswati Utami (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
The fluorescence properties of complexes of dexchlorpheniramine maleate (DXC) and erythrosine B (ERB) under buffer conditions have been observed through experiments. After the excitation was maintained at 504 nm, the emission wavelength was measured at 556 nm. The outcome demonstrated that the amount of DXC added to the mixture causes the fluorescence of erythrosine to be correspondingly quenched. This system functions best at a pH of 3.6. The research demonstrates the potential of ERB as a complexing agent for DXC quantitative analysis through complex ion formation.